Role of serum uric acid in metabolic syndrome: A cross-sectional study in central Karnataka - B M Rashmi; Basavaraj V Savadi; Bhagyajyoti; Patil Shrish (Wolters Kluwer Medknow Publications, 2023)
Background: Elevated levels of uric acid are the end product of purine metabolism. Uric acid levels are regulated by xanthine oxidase enzyme. Increased xanthine oxidase activity results in the generation of free radicals. Hence, elevated uric acid levels are the manifestations of oxidative stress. Meanwhile, raised uric acid can trigger release of inflammatory mediatory and create the inflammatory state. Thus, inflammation and oxidative stress are the important events in the pathogenesis of metabolic syndrome. This study aimed to find the association of uric acid levels with metabolic syndrome and the individual components of metabolic syndrome. Methodology: A comparative, descriptive, cross-sectional study was conducted among 50 metabolic syndrome cases and 50 controls. Clinical examination followed by laboratory investigations for the estimation of serum uric acid, fasting blood sugar, postprandial blood sugar, glycated hemoglobin, high sensitivity C-reactive protein (Hs-CRP), fasting insulin, and lipid profile. Insulin resistance (IR) was calculated by homeostatic model assessment-IR (HOMA-IR). Results: In the metabolic syndrome patients' group, serum uric acid was found to have strong positive correlation with body mass index, blood pressure, glycemic indices, IR, lipid profile, and Hs-CRP. It was found that there was 2.5 times higher risk of development of metabolic syndrome with every unit increase in serum uric acid levels and this association was found to be statistically significant. Conclusion: Uric acid can be used as the marker for the early identification of metabolic syndrome or as a prognostic marker in the diagnosed cases of metabolic syndrome.